Comparing the Effectiveness of Group Dialectical Behavior Therapy with Group Schema Therapy on Emotional Dysregulation in Women with Coronary Heart Disease - Mohammadi Lapvandani, Golriz; Karbalaei Mohammad Migoon, Ahmad; Malihialzackerini, Saied; Kalhornia Golkar, Maryam (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2022)
Background and Aim: Cardiovascular diseases are the main cause of disability and death in different countries of the world and despite the invention of various treatment methods they still have a high prevalence. Although the most important psychological factors in the development and progression of heart diseases are disputed, various researches show that psychological factors play a significant role in the development of cardiovascular diseases. The present study was conducted with the aim of comparing the effectiveness of group dialectical behavior therapy with group schema therapy on emotional dysregulation in women with coronary heart disease. Method: This was a quasi-experimental study using a pre-test-post-test design with a control group. The statistical population included women with coronary heart disease referred to Azadi Hospital in Tehran in 2018-2019, 45 of whom were selected as a statistical sample by available sampling and divided into two experimental groups and one control group (15 people for each group) were replaced. The measuring tool of the research included emotional dysregulation scale (Gratz and Romer, 2004). After completing eight sessions of group dialectical behavior therapy and eight sessions of group schema therapy in the experimental groups, the mentioned questionnaires were completed again immediately and after three months, respectively, as a post-test and follow-up in the groups. The results were analyzed using descriptive and inferential statistical methods (variance analysis test with repeated measurements) in SPSS.23 software. Results: The results of analysis of variance with repeated measurements showed that both treatments were effective on emotional dysregulation in women with coronary heart disease from the pre-test, post-test and follow-up stage (p=0.001); The results of Bonferroni’s post hoc test also showed that group dialectical behavior therapy has a greater effect than group schema therapy in reducing emotional dysregulation in women with coronary heart disease from pre-test to post-test and follow-up (p=0.001). Conclusion: training in the use of group dialectical behavior therapy is recommended as an effective intervention method in reducing emotional dysregulation in women with coronary heart disease.